The Role of Women in Empowerment and Improvement of Community Literation through Waste Management - Wahyu Kartiko Utami; Moh Rizky Godjali (Journal of Governance, 2020)
This research explained the role of women in empowerment and improvement of community literacy through waste management in Muntang Village, Kemangkon District, Purbalingga Regency. The subject of this research was a women leader in ‘Limbah Pustaka’ community namely Roro Hendarti. This research used a qualitative descriptive research method. Data collection was obtained through observation, interview, and documentation. Data were analyzed using data reduction, display and verification. The main informant in this study was Roro Hendarti as the leader of ‘Limbah Pustaka’ community, and the secondary informant was community members of Limbah Pustaka. The theory was used in this research was Astuti's (1998) women's role theory which divides women's roles into three, namely productive roles, domestic roles, and social roles. Roro Hendarti's productive role is in her role in empowering the community and the Limbah Pustaka community through the waste bank as well as training activities such as dancing, sewing, handicrafts, and so on. Domestic role is related to her role as a wife and housewife for her husband and children. Meanwhile, the social role is related to her role in increasing community literacy, especially for children in Muntang Village. Furthermore, she also helps improve their environment to reduce plastic waste. This research is expected to produce a good model or design in waste management, and later it can become an example or model for other communities in Indonesia.